Ответы и объяснения

2013-07-01T18:31:35+00:00

1) y'=-3sin3x+0.5cosx/2

2)y'=((3x²-1)*x⁵-5x⁴(x³-x))/x¹°=(3x⁷-x⁵-5x⁷+5x⁵)/x¹°=(4x⁵-2x⁷)/x¹°=(4-2x²)/x⁵

3)y'=6x⁵sinx+x⁶cosx

4)   -⅓cos3x

5)x³/3-x²/2+x|₁²=8/3-2+2-1/3+1/2-1=7/3-1/2=14/6-3/6=11/6

  • AlbuRin
  • светило науки
2013-07-02T02:28:30+00:00

1)   f ' (x) = (cos3x+sinx/2) " = -3sin3x  +1/2cosx/2

2)   f " (x)  = ((x^3-x)  /  x^5) " = ((x^2-1) / x^4) " = (x^2-1) " * x^4 - (x^2-1) * (x^4) ' =

       = 2x*x^4 -(x^2-1) * 4x^3  =  2x^5 - 4x^5 +4x^3 = -2x^5 + 4x^3

3)   f " (x)  =  (x^6 sinx) "  =  (x^6) " * sinx  +x^6 * cosx  =  6x^5 * sinx  + x^6 * cosx

 

4)   S sin3x dx  =  -1/3cos3x  +  c

 

        2                                                                       2

5)   S  (x^2-x+1) dx  =  (x^3 : 3   -   x^2 : 2   +  x) |     =    2^3 : 3  -  2^2 : 2  +  2  -1^3 : 3 + 1^2 : 2  -  1  =        1                                                                       1

                   

      =8/3  - 2 + 2 - 1/3 +1/2 - 1  =  7/3 - 1 +1/2  =   1целая 5/6